Six Cs of pandemic emergency management: A case study of Taiwan's initial response to the COVID-19 pandemic. (October 2021) - Liu, Li-Yin; Wu, Wei-Ning; McEntire, David A.
Abstract: A review of the disaster literature indicates that emergency responses to pandemics are often understudied; the current COVID-19 crisis provides an important opportunity to improve awareness and understanding about this and other contagious and disruptive diseases. With this in mind, this study examines Taiwan's response to COVID-19 because it was successful in spite of a high probability of contagion. The paper first explores the assertion that cognition, communication, collaboration, and control are vital for effective disaster response; it then indicates the need to consider two additional Cs: confidence (trust of government's competency) and coproduction (public participation in disaster transmission prevention). The paper also conducts a qualitative descriptive study of the Taiwan government's response timeline with examples of each of these concepts in action. To further illustrate the need for the two additional Cs, survey data illustrate how public confidence serves as a pivot between government's COVID-19 response and citizen coproduction in COVID-19 transmission prevention.